2003
DOI: 10.1074/jbc.m303168200
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Inhibitory Factor (LIF), Cardiotrophin-1, and Oncostatin M Share Structural Binding Determinants in the Immunoglobulin-like Domain of LIF Receptor

Abstract: Leukemia inhibitory factor (LIF),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 92 publications
2
45
1
Order By: Relevance
“…In many cell types, exogenous LIF upregulates LIFR mRNA expression [81,82]. In contrast, we observed that in response to LIF stimulation in NP cells, LIFR expression remained unchanged, but gp130 mRNA was upregulated in a concentration-dependent fashion (Fig.…”
Section: Signaling Pathways Activated By Lifcontrasting
confidence: 42%
“…In many cell types, exogenous LIF upregulates LIFR mRNA expression [81,82]. In contrast, we observed that in response to LIF stimulation in NP cells, LIFR expression remained unchanged, but gp130 mRNA was upregulated in a concentration-dependent fashion (Fig.…”
Section: Signaling Pathways Activated By Lifcontrasting
confidence: 42%
“…Structural analyses of this family of receptors revealed that high affinity binding of the cytokine to its receptor complex involves on one side the CBD of a first receptor subunit and on the other side the Ig-like domain of the second receptor component (50 -54). We previously reported that OSM binds to the CBD of gp130 and to the Ig-like domain of OSMR (52,55). In the soluble form of OSMR, the CBD located downstream from the Ig-like domain was truncated and stopped after half of the module, suggesting that this truncated portion of receptor is not able to bind a cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the CBD of some large-size cytokine receptors (gp130, IL-12R␤1, and granulocyte-colony stimulating factor) interact with the cytokine(s) through site II (57,(61)(62)(63)(64). Recruitment of an additional site of interaction (site III) located on the Ig-like domain of a second large-size receptor leads to oligomerization and signaling of the receptor complex (65)(66)(67)(68)(69). Because no Ig-like domain is present in GPL, we can hypothesize that GPL should interact with its potential ligand(s) through a site II or a site I. GPL also likely implicates a neighbor receptor holding an Ig-like module to define the site III and to allow the dimerization process of large-size signaling subunits and subsequent signaling events.…”
Section: Discussionmentioning
confidence: 99%